Serum 25-hydroxy vitamin D level is associated with elastography-detected liver fibrosis in patients with type 2 diabetes mellitus in China - Huang, Nan; Su, Xianghui; Yu, Ting; Wu, Xiaodong; Lu, Bing; Sun, Weixia; Yao, Liqin; Wang, Maoyun; Wang, Yao; Wu, Wenxuan; Liu, Yingzhao; Yang, Ting; et al. (Frontiers in Endocrinology, 2024)
Objective In this cross-sectional study including patients with type 2 diabetes mellitus (T2DM) we aimed to explore the relationship between serum 25-hydroxy vitamin (25(OH)D) level and liver steatosis and fibrosis in the Chinese population. Methods Patients visiting 16 clinical centers with T2DM were recruited. Their liver steatosis and fibrosis status were then assessed using elastography. Factors associated with steatosis and fibrosis were explored using regression analysis. Correlations between serum 25(OH)D levels and other patient characteristics were analyzed using linear regression. Results In total, 1,513 patients with T2DM were included in the study. The prevalence of steatosis and fibrosis was 69.7%, and 34.6%, separately. A lower level of 25(OH)D was detected in patients with liver steatosis compared to those without, although it was not an independent predictor of this condition. However, 25(OH)D level was independently associated with liver fibrosis even when adjusted for age, sex, body mass index, hemoglobin A1c, insulin, and homeostatic model assessment of insulin resistance (OR = 0.964 [0.935-0.993], P = 0.015). When patients were separated into subgroups by sex, a correlation between 25(OH)D and fibrosis was identified in the male group (OR = 0.969 [0.940-0.998], P = 0.038). Conclusions In conclusion, this multi-center, cross-sectional study in patients with T2DM showed that serum 25-hydroxy vitamin D level was strongly associated with liver fibrosis and this relationship was more pronounced in male patients. Clinical trial registration https://clinicaltrials.gov/ct2/show/, identifier NCT05597709.